(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The presence in Italy of Cydia johanssoni Aarvik & Karsholt, 1993, was reported for first time, furthermore the female of the species was described. C. johanssoni is closely to the multistriana group species, section multistrianae, though matching Cydia blackmoreana (Walsingham, 1903). The genitalia of C. johanssoni and C. blackmoreana are very similar. In the female genitalia the following differences are noted: ostium in C. johanssoni narrower than in C. blackmoreana, becoming broader posteriorly. Median portion of VII sternite proportionally smaller in C. joahanssoni than in C. blackmoreana, in the former it is about the same length as the ostium, whereas in C. blackmoreana it is about 1.5 the length of ostium. Ductus bursae is longer in C. blackmoreana than in C. johanssoni. The adult and genitalia of both sexes are figured.